Specific Features of Heatand Mass Transfer Processes in Road Dressings - B. M. Khroustalev; Tingguo Liu; V. D. Akeliev; Yu. H. Aliakseyeu; Jicun Shi; V. V. Zankovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
The paper presents a fragment of on-going investigations directed on creation of optimum data environment that ensures an access to world scientific journals and other publications which are necessary for qualitative implementation of works on priority directions of R&D in the field of road-construction industry in the period of 2016–2020. A citation analysis has been applied while using data of Journal Citation Reports for selection of world scientific serial publiccations which are necessary for execution of investigations on heat and mass transfer in road dressings. The road dressings are considered as open heterogeneous thermodynamic systems. Their deformations occur under various climatic conditions due to heat and mass transfer processes and interaction of transport flows and road surface. Crack formation takes place in depth of the road dressings and on road surfaces as a result of temperature, mass transfer processes. As it is known material structure of constructive layers especially which are created with the help of technogenic wastes (asphalt-concrete, concrete, reinforced concrete scrap and products of its recycling, brick rubble, various wastes of production etc.) influence on heat and mass transfer. The paper presents results of investigations on heat flows, boundary layers according to air viscosity, velocity of geometric permeability characteristics, capillary pressures in road pavements.